Corporate finance : banking and capital markets. - College of Law (London, England) (Bristol [England] : Jordans)
Explores the fundamentals behind drafting loan facility documentation, fundamental issues in secured lending and capital market financing.
Description based on: 1997/98.
Issued by: The College of Law.
oif 05/03/15
Ref.
Keywords: Corporations -- Finance -- Law and legislation -- Great Britain; Capital market -- Law and legislation -- Great Britain; Banking law -- Great Britain